Pentaaqua(4,6-dihydroxybenzene-1,3-disulfonato-κO1)zinc pentahydrate - Zhu, Zhi-Biao (International Union of Crystallography, 2012)
The Zn II atom in the title complex, [Zn(C 6H 4O 8S 2)(H 2O) 5] ·5(H 2O), is coordinated by five water mol-ecules and an O atom of a 4,6-dihy-droxy-benzene-1,3-disulfonate dianion. The coord-ination geometry is distorted octa-hedral, with the Zn-O sulfonate bond relatively long compared to the Zn-O water bonds. The coordinated and lattice water mol-ecules inter-act with each other and with the hy-droxy groups and sulfonate ligand through O-H⋯O hydrogen bonds, generating a tightly held three-dimensional network.